2013
DOI: 10.1002/dev.21127
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in reward behavior in adolescent and adult rats

Abstract: Compared to adults, adolescents are at heightened risk for drug abuse and dependence. One of the factors contributing to this vulnerability may be age-dependent differences in reward processing, with adolescents approaching reward through stimulus-directed, rather than goal-directed, processes. However, the empirical evidence for this in rodent models of adolescence, particularly those that investigate both sexes, is limited. To address this, male and female rats that were adolescents (P30) or adults (P98) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 87 publications
13
67
1
Order By: Relevance
“…In the present study, the more rapid acquisition of Pavlovian conditioned approach in SD females was only evident for the first few days of training, and there was no difference between sexes in terminal performance, consistent with findings using sucrose [23]. Many factors could contribute to this sex difference in performance, including motivation [50], attention [51, 52], learning [53, 54], impulsivity [52, 55, 56] or even differences in activity/exploration [5760].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the more rapid acquisition of Pavlovian conditioned approach in SD females was only evident for the first few days of training, and there was no difference between sexes in terminal performance, consistent with findings using sucrose [23]. Many factors could contribute to this sex difference in performance, including motivation [50], attention [51, 52], learning [53, 54], impulsivity [52, 55, 56] or even differences in activity/exploration [5760].…”
Section: Discussionsupporting
confidence: 90%
“…There is, however, a great deal of clinical and preclinical research indicating that females are more responsive to both nondrug [23, 24] and drug rewards than are males [2533], and that this increased responsive may be due to circulating sex hormones [34]. Drug self-administration studies have shown that females respond more than males through extinction and reinstatement procedures [35].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adults, adolescent rats display a learning deficit on a delayed alternation task and commit a greater number of perseveration errors (Koss et al, 2011). Additionally, across several tasks, adolescent rats are less sensitive to extinction or reward devaluation compared with adults (Sturman et al, 2010; Andrzejewski et al, 2011; Naneix et al, 2012; Hammerslag & Gulley, 2014), suggesting an impairment in impulse control and behavioral inhibition. These studies collectively suggest that in both humans and rats, PFC maturation during adolescence coincides with decreases in perseverative responding and inhibitory control, functions that are dependent on PFC interactions with other parts of the limbic system such as the basolateral amygdala.…”
Section: Behavioral Changes and Hormone Effectsmentioning
confidence: 99%
“…Therefore, we believe preadolescent is a more specific term that does not imply whether the rodents have been weaned or not. Since the seminal review by Spear (2000), rodent adolescence has been broadly defined to be P28 -P60, an age range utilised by many preclinical studies of anxiety and addiction [61][62][63][64]. These redefined developmental stages have already been referred to in previous papers (e.g., [65,66]) and are summarised in Figure 1.…”
Section: Developmental Stages In Humans and Rodentsmentioning
confidence: 99%